A multidisciplinary approach to health campaign effectiveness - Jessica M. Rath; Marisa Greenberg; Ollie Ganz; Lindsay Pitzer; Elizabeth Hair; Haijun Xiao; Jennifer Cantrell; Donna Vallone (SAGE Publishing, 2018)
Campaign costs are rising, making ad execution testing more critical to determine effectiveness prior to media spending. Premarket testing occurs prior to messages' airing while in-market testing examines message attributes when messages are aired within a real-world setting, where context plays an important role in determining audience response. These types of ad testing provide critical feedback to help develop and deploy campaigns. Due to recent changes in media delivery platforms and audience tobacco use behavior, this study analyzes two nationally representative youth samples, aged 15-21, to examine if pre-market ad testing is an indicator of in-market ad performance for public health campaigns, which rely on persuasive messages to promote or reduce health behaviors rather than selling a product. Using data from the truth® campaign, a national tobacco use prevention campaign targeted to youth and young adults, findings indicate strong associations between pre-market scores and in-market ad performance metrics.